The Effectiveness of Compassion-focused Therapy on Integrative self-knowledge, Self-destructive behaviors and Fatigue in Drug Users - Alijani, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The purpose of this study was to examine the efficacy of compassion-focused therapy in addressing psychological coherence, self-destructive behavior, and fatigue among drug users. Methods and Materials: The present study was semi-randomized in terms of its purpose, application, and research method, with a pre-test, post-test, and follow-up design with a control group. Among the addicts referred to the Paris addiction treatment center in Tehran in 2021, 30 people which was included in the study were selected and replaced randomly (by lottery) in the experimental group (15 people) and the control group (15 people). The experimental group received compassion-focused therapy during eight sessions, and the control group did not receive therapy. To collect data, the short form of Antonoski’s psychological coherence scale (SOC-13), the self-destruction questionnaire of Sanson et al. (SHI), and the fatigue questionnaire of Smets et al. (MFI) were used. Findings: The results of the research showed that between the scores of psychological coherence, self-destruction, and fatigue in the treatment group focused on compassion and the control group in the post-test, there was a significant difference in follow-up (p < 0.05). Therefore, is effective in increasing psychological coherence and reducing self-destruction and fatigue in drug users. Conclusion: As mentioned, the results indicate that compassion -focused therapy is effective for enhancing psychological cohesion, reducing self-destructive tendencies, and addressing fatigue among substance abusers. Additionally, based on the effect size analysis, it was determined that this treatment has a particularly significant impact on psychological cohesion and self-destructive behavior. Therefore, its utilization is strongly recommended for clinical psychologists and psychotherapists aiming to enhance psychological coherence and decrease self-destructive tendencies in individuals with substance use issues.